Restorative Dentistry : an Integrated Approach. - Jacobsen, Peter (John Wiley & Sons, 2009)
Restorative Dentistry: An Integrated Approach presents the core of knowledge that forms the basis of clinical practice in restorative dentistry. The book contains a practical common-sense approach to clinical problems structured within the limitations imposed by the patient and the ability and facilities of the dentist. Subjects included in the book are Periodontology, Endodontics, Dental Biomaterials, Oral Biology and Pathology, and Fixed and Removable Prosthodontics. However Restorative Dentistry offers a somewhat unique approach in that it integrates the basic sciences that are fundamental.